Metabolic syndrome severity z-score in non-diabetic non-obese Egyptian patients with chronic hepatitis c virus infection - Safaa R. Askar; Radwa S. Hagag; Moamen A. Ismail; Heba I. Aly (SpringerOpen, 2024)
Abstract Background The risks of heart disease, resistance of insulin, and diabetes mellitus type II are increased in individuals diagnosed with metabolic syndrome. Furthermore, there is an increase in the vascular and neurological effects. This study aimed to assess the isolated independent impact of hepatitis C virus (HCV) on metabolic syndrome, excluding obesity and diabetes mellitus as common risks, this impact was assessed using the metabolic syndrome Severity Z-score (MetS Z-Score) which was initially designed to assess metabolic disease severity itself. Fifty-one HCV patients non-obese and non-diabetic who visited the Tropical Medicine Department from July 2023 to June 2024 were included in our prospective cross sectional study. Results After calculation of MetS Z-Score, strong correlations were observed between MetS Z-score and the following data: HDL, fasting insulin, fasting blood sugar, HOMA-IR and hypertension (P value < 0.05). Moreover, The MetS Z-Score was found to have higher values in hypertensive patients. Jaundice shows a near to significance correlation with the MetS Z-Score. Anemia, hypoalbuminemia and thrombocytopenia were observed in the included HCV patients. Low density lipoprotein, alanine aminotransferase, aspartate aminotransferase, cholesterol and triglycerides have shown higher levels than normal in the included HCV patients. Conclusion The MetS Z-score can be used for determining the severity of metabolic abnormalities in HCV patients who are neither diabetic nor obese.